Impact of Farmers’ Knowledge and Agricultural Practices on the Occurrence of Fungal Diseases in Pepper Crops within the Northern Guinea Savannah Ecological Zones of Nigeria - B.G, Zakari; I.B, Chimbekujwo; Z.G. , Jimeta; Talba, Usman (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Pepper (Capsicum spp.) is cultivated in the Northern Guinea Savannah ecological zone of Nigeria which faces significant challenges due to the prevalence of fungal diseases. This study identified the agronomic practices influencing the occurrence and intensity of these diseases. Conducted in Jalingo and Yola from May 2019 to October 2020, the research incorporated a household survey and a field survey to comprehensively assess the dynamics of the disease. The majority of farmers (37.5%-40%) were aged 31 - 40, predominantly young and middle-aged. A significant gender disparity existed, with 97.5 % - 100 % male farmers. Married farmers comprised 65 % - 70%, indicating family labor availability. Lack of formal education was notable, with 60 % - 47.5 %. The average household size was 8 persons, supporting family labor. Occupation-wise, 47 % - 57 % were traders, 40 % - 30 % relied on farming, and 5 % each were civil servants. Seed sourcing revealed 60 % - 42.5 % used seeds from their farms, and 5 % - 10 % used certified seeds. Mixed cropping was prevalent (57.5 % - 62.5 %). Crop rotation involved tomatoes or garden eggs (40 % - 42.5 %). Synthetic pesticides were used by 57.5 % - 60 %, while 22.5 % - 27.5 % controlled weeds regularly. The study emphasizes the high prevalence of fungal diseases, especially vascular wilt and anthracnose, in pepper crops. Farmers, facing financial constraints and limited education, were engage in practices contributing to disease spread. Education and sensitization initiatives will enhance agronomic practices and minimize disease spread, aiming at sustainable pepper production in the zone.